Environmental MCS package, perceived environmental uncertainty, and green performance: in green dynamic capabilities and investment in environmental management perspectives - Bresciani, Stefano; Rehman, Shafique Ur; Alam, Gazi Mahabubul; Ashfaq, Khurram; Usman, Muhammad (Emerald, 2022)
Purpose: The organizations focus on environmental factors as stakeholders exert pressure to reduce the environmental influence arising from production tasks. This study aims to see the influence of the environmental management control system (MCS) package and perceived environmental uncertainty on green performance with the mediating role of green dynamic capabilities in Pakistani manufacturing organizations. Moreover, this study aims to see the moderating role of investment in environmental management between green dynamic capabilities and green performance. Design/methodology/approach: The partial least square structural equation modeling technique is used to test hypotheses. The data was collected through questionnaires using simple random sampling, and a total of 404 questionnaires were used in the final analysis. The data was collected from September 2021 to November 2021. Multiple regression analysis followed to see the influence of environmental MCS package, perceived environmental uncertainty, green dynamic capabilities and investment in environmental management on green performance. Findings: Environmental MCS package, green dynamic capabilities and investment in environmental management are positively related to green performance. Despite this, perceived environmental uncertainty is negatively related to green performance. Moreover, green dynamic capabilities significantly mediate between environmental MCS package, perceived environmental uncertainty and green performance. Finally, investment in environmental management significantly moderates between green dynamic capabilities and green performance. Practical implications: This research covers vital issues that how top management uses the environmental MCS package, perceived environmental uncertainty, green dynamic capabilities and investment in environmental management in determining green performance. Originality/value: This research adds value to the existing literature by focusing on predictors that determine green performance. This pioneering study observes the influence of environmental MCS package and perceived environmental uncertainty on green performance and green dynamic capabilities as mediators by applying natural resource-based view theory. Moreover, investment in environmental management is used as a moderator between green dynamic capabilities and green performance. Finally, this study can benefit management, industrial policymakers and academicians.